Mutational landscape of normal epithelial cells in Lynch Syndrome patients - Bernard C. H. Lee (Nature Communications, 2022)
It is unclear whether somatic mutation rates are elevated in Lynch Syndrome (LS), which is the most common cause of hereditary colorectal cancer. Here, the authors use whole-genome sequencing and organoid cultures to show that normal tissues in LS patients are genomically stable, while ancestor cells of neoplastic tissues undergo multiple cycles of clonal evolution.